Microbiological quality of food contact surfaces (Spoons) at selected restaurants in Klang Valley, Malaysia - Nahar, Naili; Mahyudin, Nor Ainy (Penerbit Universiti Kebangsaan Malaysia, 2018)
Food borne diseases increase worldwide and contamination of food contact surfaces serves as one of the reasons for their occurrence. The aim of this study was to determine the microbiological quality of spoons at selected restaurants in Klang Valley, Malaysia. Five restaurants were selected therein for the study. They were respectively labelled A, B, C, D and E. A total of 150 cleaned spoons (30 spoons from each restaurants) that were ready to be used by customers at the restaurants were examined. Total plate counts (CFU/cm2) of the spoons were determined; the presumptive and confirmatory tests for the presence of Escherichia coli on the spoons were also conducted. The samples were collected by surface swabbing. The result showed that restaurant C and B had the highest and lowest total plate counts (TPC), respectively. Samples from 3 of the 5 selected restaurants (restaurants C, D and E) showed positive results for the presence of E. colimainly due to poor dishware cleansing. On the contrary, negative results for the presence of E. coli at restaurant A and B were associated with the advance cleaning procedure, which used more hygienic method with dishwashers